Analisis Penerapan Keterampilan Reinforcement Oleh Guru PAK dalam Proses Pembelajaran Tingkat SMP Tahun Pembelajaran 2024/2025 - Simatupang, Ronny (Jurnal Christian Humaniora, 2025)
This study aims to determine the Analysis of the application of reinforcement skills by PAK Teachers in the learning process at the junior high school level in the Ministry of Religion of Toba Regency in the 2024/2025 Academic Year. The population of this study was all PAK teachers at the junior high school level in the Ministry of Religion of Toba Regency, totaling 146 people. The sample in the study was 20% of 146 = 28 people. Based on the data analysis test, the application of reinforcement skills by PAK Teachers in the Learning process at the junior high school level in the Ministry of Religion of Toba Regency in the 2024/2025 Academic Year in general was 96.46% and was categorized as very strong. From the hypothesis test, it is known that the t_count test = 47.53 ≥ t_table28-1,a = 5% is 1.701, where t_count ≤ t_table is 47.537 1.70. Thus Ha is accepted and Ho is rejected, meaning that the Analysis of the Application of Reinforcement Skills by PAK Teachers in the Learning Process at the junior high school level in the Ministry of Religion of Toba Regency TP. 2024/2025 ≥ 75% of expected.